(untitled) (Journal of Hama University, 2019)
The research was performed at Faculty of Agricultural-Basatin Abu Jarash-during the period 2016-2017 in order to study the effect of foliar in potassium and boron on saffron growth and productivity .The experiment showed a significant superiority of treatment of foliar(Boron1 _B1)(10mg/L)dry weights of the stigmas ,length of stigmas, The number of flowers, the number of shoots, the number of corms, and the weight of corms, each of were0.025g,3.3cm,5.333flower, 2.46, 2.6667cm,9.433g respectively, compared to the control. whereas the treatment of( potassium2+ boron2_K2B2)(2g/L+20 mg/L) was significantly higher than the number of corms .Also the treatment (2g/L+20mg/L) was significantly superior to the control in the weight of the petals .It was 0.433g and the treatment of( boron 2 _B2)(10mg/L) was significantly higher than the length of the leaves. Treatment (potassium1+boron2 _K1B2)(3 g/L+10mg/L)was superior to the number of leaves with 21sheets.